FAKTOR-FAKTOR YANG MEMENGARUHI KONSERVATISME AKUNTANSI - Rojwaa Taqiyah Zahro; Aan Marlinah; Dicky Supriatna (E-Jurnal Akuntansi TSM, 2022)
The objective of this research is to obtain empirical evidence about the influence of leverage, firm size, managerial ownership, size of board commissioners, profitability, financial distress and litigation risk as independent variables to accounting conservatism as dependent variables. This research used companies listed in nonfinancial companies sector in the Indonesian Stock Exchange from 2019 until 2021. 110 companies meet the criteria by using a purposive sampling method and using 330 data. This research uses multiple regression methods for data analysis. The result shows that leverage,firm size, managerial ownership, size of board commissioners, profitability, financial distress and litigation risk have no influence to accounting conservatism principle in the company.